Sustainability Education: Possibilities Across Higher Education - Jay M. Shuttleworth (The University of Alabama, 2022)
Jones, P., Selby, D. & Sterling, S. (Eds.) (2010). Sustainability Education: Perspectives and Practice Across Higher Education. London: Earthscan. 2010. ISBN 978-1-84407-877-6